2016
DOI: 10.1186/s13019-016-0484-1
|View full text |Cite
|
Sign up to set email alerts
|

Single chest tube drainage is superior to double chest tube drainage after lobectomy: a meta-analysis

Abstract: BackgroundIn this meta-analysis, we conducted a pooled analysis of clinical studies comparing the efficacy of single chest tube versus double chest tube after a lobectomy.MethodsAccording to the recommendations of the Cochrane Collaboration, we established a rigorous study protocol. We performed a systematic electronic search of the PubMed, Embase, Cochrane Library and Web of Science databases to identify articles to include in our meta-analysis. A literature search was performed using relevant keywords. A met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 9 publications
0
24
0
1
Order By: Relevance
“…Generally speaking, chest tube drainages were usually applied for patients suffering from pneumothorax who should be admitted to hospital following the failure of needle aspiration (3). And other indications for chest tube drainage included hemothorax (49,50), pleural effusion (51-53), pleural empyema (54,55), and major thoracic surgery (56)(57)(58). The approaches to insert chest tube drainage into body parts include axillary or anterior approach.…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, chest tube drainages were usually applied for patients suffering from pneumothorax who should be admitted to hospital following the failure of needle aspiration (3). And other indications for chest tube drainage included hemothorax (49,50), pleural effusion (51-53), pleural empyema (54,55), and major thoracic surgery (56)(57)(58). The approaches to insert chest tube drainage into body parts include axillary or anterior approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not find any significant relationship between surgeon experience and tube size, only that 28‐Fr was most common. It is also noteworthy that a meta‐analysis by Zhou et al . found that using a single ICC post‐lobectomy did not increase post‐operative complication and re‐drainage rates compared to using two ICCs, but did reduce post‐operative pain and hospitalization times.…”
mentioning
confidence: 99%
“…Meanwhile, by observing the amount, characteristics of drainages, and the fluctuation of the water column, some abnormal conditions can be found and treated in time [29]. At present, it is common that SCD is placed after lobectomy of upper lung tissue in China, while DCD are placed after lobectomy of lower lung tissue [14]. The potential reason is that the closure of the residual cavity after lobectomy depends on adequate drainage with aims to promote lung expansion and avoid mediastinum displacement [30].…”
Section: Discussionmentioning
confidence: 99%